2021
DOI: 10.2478/jhp-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

“You’re only a carrier” – women and the language of haemophilia

Abstract: Women who have the gene variant for haemophilia are labelled solely as ‘carriers’ unless they have a factor VIII activity of ≤40%. This term, which describes an individual who can pass on a disorder but are themselves unaffected, reflects a legacy that extends from the 18th century to the present day. There is strong evidence that women labelled as carriers experience heavy periods, joint damage, pain and impaired quality of life. The label ‘carrier’ does not recognise this burden and is associated with guilt,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This was also recognised by Choi et al., who report women becoming aware of diagnosis only after delivery of an affected child and limited healthcare provider knowledge, information and support 9 . This is consistent with the difficulties WHC face 4,5,7,10 and most of these themes were shared by WBD. The Cinderella Study has highlighted the problems women encounter pre‐ and post‐diagnosis, even in known families, and endorses the ten principles of care formulated by specialists and patients' representatives to support timely, accurate diagnosis and equitable care to men, with recognition of the additional challenges faced by WBD 6 …”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This was also recognised by Choi et al., who report women becoming aware of diagnosis only after delivery of an affected child and limited healthcare provider knowledge, information and support 9 . This is consistent with the difficulties WHC face 4,5,7,10 and most of these themes were shared by WBD. The Cinderella Study has highlighted the problems women encounter pre‐ and post‐diagnosis, even in known families, and endorses the ten principles of care formulated by specialists and patients' representatives to support timely, accurate diagnosis and equitable care to men, with recognition of the additional challenges faced by WBD 6 …”
Section: Discussionsupporting
confidence: 68%
“…1 In 2011, a Canadian study reported negative experiences with specialist and non-specialist HCPs amongst women diagnosed as haemophilia carriers. 10 It is disappointing to find that these problems are still prevalent today. There is a need to raise awareness about bleeding disorders amongst all HCPs and to empower affected women through education and advocacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation